(untitled) (Applied Biological Research, 2020)
The potential plant growth promoting rhizobacterium Serratia liquefaciens isolate KM2 (SL-KM2) was evaluated for its effect on the growth and hormonal homeostatic in rice cv. ‘Dandi’. The rice seeds were treated with SL-KM2 and sown in po;ybags. The phytohormonal analysis of rice seedlings was performed 20 days after sowing (DAS) by using UFLC techniques. The study showed that SL-KM2 seed treatment balanced phytohormones homeostatic wherein gibberellic acid (GA3) and indole acetic acid (IAA) contents in leaves and root tissues were affected positively whereas abscisic acid (ABA) and jasmonic acid (JA) were negatively affected. The balanced phytohormone contents resulted in improvement in physiological parameters viz., root length, root volume, shoot length and fresh weight as compared to the untreated control. The expression analysis of genes involved in phytohormones perceptionand signaling was performed by qRT-PCR technique at 20 DAS which furtherconfirmed seed treatment-mediated hormonal modulation. Under seed treatment condition, the genes GAI1, EIL1, PR1, PAL, EDS1 and AOS2 were up-regulated in leaf tissue whereas ERF1 gene was down-regulated. In case of root tissue, genes GAI1, EIL1, ERF1, PAL and EDS1 were up-regulated whereas genes PR1 and AOS2 were down-regulated. Besides improving the seedling physiology, the up-regulation of PAL and PR1 by SL-KM2 seed treatment imparted better stress tolerance in plant. This study confirms the association of phytohormone-related gene expression with observed hormonal state contributing toward enhanced physiological response in rice.